The Implementation of IDDSI Framework in Irish Residential Healthcare Settings: A Survey - Ibrahaem Allithey, Mona (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2022)
Background The International Dysphagia Diet Standardization Initiative (IDDSI) was found to standardize the terminology of diet modification for people living with dysphagia. Diet modification plays a vital role in managing dysphagia. It is a safe way to facilitate and maintain nutritional needs orally for people with swallowing disorders. To date, studies investigating the feasibility of IDDSI utilization in a residential healthcare setting are lacking. In this study, IDDSI implementation is overviewed in Irish residential healthcare settings. Also, the barriers and facilitators for its implementation are determined from the perspective of a whole country. Aims This study centers on 1) identifying positive and negative factors that contribute or do not contribute to IDDSI implementation, 2) evaluating how widely IDDSI is implemented in Irish residential healthcare settings, and 3) determining factors involved in its implementation. Methods & Procedures A cross-sectional, descriptive study using an online questionnaire, disseminated via Qualitrics, was employed. The participants included healthcare workers interested in IDDSI implementation and working in hospitals, hospices, and nursing homes. Data collection took place between March and April 2021. Results Thirteen SLTs responded to the survey. Most of the findings were from hospitals and community settings. The findings showed that lack of time, training, teamwork, and reduced awareness impeded IDDSI implementation. The most common responses of the implementation facilitators were staff training using online tools, teamwork with MDT members, and using IDDSI resources and posters. Participants confirmed that the IDDSI facilitated communication between professionals, and it is invaluable for patients overall. Conclusion This study contributes to a better understanding of IDDSI implementation. Most responses emphasized similar points, which indicates the importance of IDDSI implementation in healthcare settings for dysphagia management. These results are valuable for clinical practice and future research.